Effect Of Different Heavy Metals And Ph On Α-Amylase Production From Bacillus Amyloliquefaciens - NEERAJ SHARMA; RASHMI VAMIL (International Journal of Pharma and Bio Sciences, 2012)
Microbial enzymes are used in the many industries like textile industries, food industries, pharmaceutical industries, paper industries etc. Alpha- amylase is one of these enzymes. The effects of different parameters like different pH and heavy metals concentration on alpha-amylase production by Submerged fermentation were examined. The present investigation concerned with the production of α-amylase by Bacillus amyloliquefaciens. The fermentation was carried out in by continuous shaking containing 50 ml of medium in 250 ml flask. The incubation time was 72 h; incubation temperature (37°C) and size of inoculums (0.05ml) were also optimized. The optimum pH for production of α-amylase was detected at pH 7.5. Effects of different heavy metals were noted and it was found that production of α-amylase was strongly inhibited by Cu²âº but less affected by Mg²âº, Fe²âº, and Mn²âºat higher concentrations.